Comprehensive biomarker analysis of long-term response to trastuzumab in patients with HER2-positive advanced gastric or gastroesophageal adenocarcinoma. (April 2023) - Porth, Isabel; Hirsch, Daniela; Ceribas, Yonca; Weidner, Philip; Weichert, Wilko; Götze, Thorsten Oliver; Perner, Sven; Luley, Kim; Heyer, Christian Moritz; de la Torre, Carolina; Hofheinz, Ralf-Dieter; Lorenzen, Sylvie; et al.
Abstract: Background: A subgroup of patients with HER2-positive metastatic gastric and gastroesophageal junction cancers shows long-term response under trastuzumab maintenance monotherapy. Obviously, HER2 status alone is not able to identify these patients. We performed this study to identify potential new prognostic biomarkers for this long-term responding patient group. Patients and methods: Tumour samples of 19 patients with HER2-positive metastatic gastric and gastroesophageal junction cancer who underwent trastuzumab treatment were retrospectively collected from multiple centres. Patients were divided into long-term responding (n = 7) or short-term responding group (n = 12) according to progression-free survival (PFS≥12 months vs. PFS < 12 months). Next-generation sequencing and microarray-based gene expression analysis were performed along with HER2 and PD-L1 immunohistochemistry. Results: Long-term responding patients had significantly higher PD-L1 combined positive scores (CPS) and CPS correlated with longer progression-free survival. PD-L1 positivity (CPS ≥ 1) was further associated with an increased CD4+ memory T-cell score. The ERBB2 copy number as well as the tumour mutational burden could not discriminate between short-term and long-term responding patients. Genetic alterations and coamplifications in HER2 pathway associated genes such as EGFR, which were connected to trastuzumab resistance, were present in 10% of the patients and equally distributed between the groups. Conclusion: The study highlights the clinical relevance of PD-L1 testing also in the context of trastuzumab treatment and offers a biological rational by demonstrating elevated CD4+ memory T-cells scores in the PD-L1-positive group. Highlights: Identify potential new prognostic biomarkers for trastuzumab long-term response. Retrospective study of HER2-positive gastric cancer patients treated with trastuzumab. Biomarker analysis using immunohistochemistry, NGS and gene-expression analysis. PD-L1 expression has clinical relevance for HER2-positive gastric cancer. PD-L1 positivity was associated with higher CD4+ memory T-cell scores.